Concepção detalhada de uma bancada para simular esforços mecânicos em colunas de perfuração - Costa, Luan Wangara Inguaggiato [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this work we study the construction of a test rig made to simulate the Mechanical efforts in wich a drillstring is submitted. The model is based on the rig built at IDS, Germany. There are some fault liabilities while doing the project of the axis. Therefore it's important to analyze and take knowledge of this efforts in order to predict failures like rupture or fatigue collapse. The main objective of this theis is to show the operating principle of the test rig and it's construction. The accomplished study allow us to predict the drillstring behavior and from the economic point of view that is very important because failures results in equipments maintenance that requires time and money causing prejudice to the company. Using SolidWorks, a simulation software, the thesis approaches all the mechanical parts required for it's construction as well as it's working principle. Acquisition sensors like strain gauges, accelerometer, and torque transductor were also used in this model. The objective of this thesis is to create a simulation model to be eventually at FEG(UNESP). During the development of the study, it was possible to learn more about the drilling process and the mechanical efforts in which the drill pipe is submitted. The accomplished contributed with knowledge for the student in the drilling process area. Also during the development of the study it was possible to have contact with different areas of engineering but the study is specifically directed to the construction of the test rig. Therefore the main theme of this thesis is to show the operating principle of the test rig and it's construction
Keywords: Perfuração e broqueamento; Fadiga - Simulação por computador; Torque; Drilling and boring